1983
DOI: 10.1111/j.1445-5994.1983.tb02607.x
|View full text |Cite
|
Sign up to set email alerts
|

A COMPARISON OF LOW DOSE LEVAMISOLE and PENICILLAMINE IN RHEUMATOID ARTHRITIS

Abstract: Levamisole (150 mg once weekly) was compared with penicillamine (250 mg daily) in a single blind independent observer study in 28 patients with rheumatoid arthritis over twelve months. Fifty percent (8/16) of patients stopped levamisole, five within three months of starting, while only two of twelve stopped penicillamine. In those patients able to tolerate treatment for twelve months, both regimens produced a significant and comparable reduction in disease activity, with the onset of action of penicillamine oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…A total of 29 interventions among 132 randomized clinical trials (RCTs) represented by 130 publications (mean [range], 71.0% [27.0%-100%] females in studies; mean [range] of ages in studies, 53 [36-70] years) were identified, which included 13 260 patients with rheumatoid arthritis. The number of studies with measured outcomes was 118 studies for TJC, 116 studies…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 29 interventions among 132 randomized clinical trials (RCTs) represented by 130 publications (mean [range], 71.0% [27.0%-100%] females in studies; mean [range] of ages in studies, 53 [36-70] years) were identified, which included 13 260 patients with rheumatoid arthritis. The number of studies with measured outcomes was 118 studies for TJC, 116 studies…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows a flowchart of the identification of the pool of RCTs. We included 131 publications, which represented 133 studies. In 1 study, the 2 interventions (sulfapyridine and 5-aminosalicylic acid) were not connected to the network.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations